An Analysis of Factors Associated with Productivity of Dryland Crops in Haryana (Indian Journal of Extension Education, 2012)
Dryland farming plays an important role in agricultural production of the country. It is a way of life for a majority of Indian farmers. It is characterized by the resource poor, small and marginal farmers, a poor infrastructure and low investments in technology and inputs. Research indicated that, not more than 20-22 per cent of modern scientific technologies have been adopted by the farming community due to one or the other reasons. It is inevitable that the second green-revolution has to come from the dryland farming and accordingly the application of technology, inputs and investments has to be tailored to convert these so-called “grey areas into green”. Resource conserving technologies are the recommended practices/technologies for efficient conservation of soil and water for maximization of the productivity of crops under dryland situation. Rapeseed & mustard, gram and bajra are the major crops grown in Rabi and Kharif season, respectively, in dry farming zone of South West Haryana. The average productivity of rapeseed and mustard, gram and bajra is quite low. This study highlighted that the adoption of crop production technologies in cultivation of rapeseed and mustard, gram and bajra crops was low under dryland farming situation. Keeping the importance of sustaining the yields of dryland crops, a study was undertaken to understand the contribution of independent variables to the productivity of rapeseed & mustard, gram and bajra crops under dryland farming situation in South-West Haryana. The results of the study highlighted that the total variation contributed by the all variables was found to be nearly 78 per cent in rapeseed and in case of mustard and gram 56 per cent. The full adoption of crop production technologies is very important in achieving desired level of productivity of dryland crops. The farmers should be educated and trained through various extension methodologies in order to adopt full package of recommended dryland farming technologies